Programmable Macrophage Vesicle Based Bionic Self‐Adjuvanting Vaccine for Immunization against Monkeypox Virus - Weiqiang Lin; Chenguang Shen; Mengjun Li; Shengchao Ma; Chenxin Liu; Jialin Huang; Zuning Ren; Yuechao Yang; Minghai Zhao; Qiulin Xie; Shuang Guo; Wei Wang; et al. (Advanced Science)
Abstract The emergence of monkeypox has become a global health threat after the COVID‐19 pandemic. Due to the lack of available specifically treatment against MPV, developing an available vaccine is thus the most prospective and urgent strategy. Herein, a programmable macrophage vesicle based bionic self‐adjuvanting vaccine (AM@AEvs‐PB) is first developed for defending against monkeypox virus (MPV). Based on MPV‐related antigen‐stimulated macrophage‐derived vesicles, the nanovaccine is constructed by loading the mature virion (MV)‐related intracellular protein (A29L/M1R) and simultaneously modifying with the enveloped virion (EV) antigen (B6R), enabling them to effectively promote antigen presentation and enhance adaptive immune through self‐adjuvant strategy. Owing to the synergistic properties of bionic vaccine coloaded MV and EV protein in defensing MPV, the activation ratio of antigen‐presenting cells is nearly four times than that of single antigen in the same dose, resulting in stronger immunity in host. Notably, intramuscular injection uptake of AM@AEvs‐PB demonstrated vigorous immune‐protective effects in the mouse challenge attempt, offering a promising strategy for pre‐clinical monkeypox vaccine development.